Survey of CAMHS clinicians about their experience of remote consultation: brief report. Issue 1 (13th January 2021) - Bhardwaj, Anupam; Moore, Anna; Cardinal, Rudolf N.; Bradley, Carol; Cross, Lauren; Ford, Tamsin J.
Abstract : The Covid-19 crisis necessitated rapid adoption of remote consultations across National Health Service (NHS) child and adolescent mental health services (CAMHS). This study aimed to understand practitioners' experiences of rapid implementation of remote consultations across CAMHS in one NHS trust in the east of England. Data were collected through a brief questionnaire documenting clinicians' experiences following remote delivery of services. The questionnaire began before 'lockdown' and focused on assessment consultations ( n = 102) as part of a planned move to virtual assessment. As the roll-out of remote consultations was extended at lockdown, we extended the questionnaire to include all remote clinical contacts ( n = 202). Despite high levels of initial concern, clinicians' reports were positive overall; importantly, however, their experiences varied by team. When restrictions on face-to-face working are lifted, a blended approach of remote and face-to-face service delivery is recommended to optimise access and capacity while retaining effective and safe care.